Pre-publication revisions of bank financial statements: A novel way to monitor banks? - Guettler, Andre; Naeem, Mahvish; Norden, Lars; Van Doornik, Bernardus (Journal of Financial Intermediation, 2024)
We investigate whether pre-publication revisions of bank financial statements contain forward-looking information about bank risk. Using 7.4 million observations of monthly financial reports from all banks in Brazil during 2007–2019, we show that 78 % of all revisions occur before the publication of these statements. The frequency, missing of reporting deadlines, and severity of revisions are positively related to future bank risk. Using machine learning techniques, we provide evidence on mechanisms through which revisions affect bank risk. Our findings suggest that private information about pre-publication revisions is useful for supervisors to monitor banks.